2021
DOI: 10.3390/cancers13112724
|View full text |Cite
|
Sign up to set email alerts
|

A Novel off-the-Shelf Trastuzumab-Armed NK Cell Therapy (ACE1702) Using Antibody-Cell-Conjugation Technology

Abstract: Natural killer (NK) cells harbor efficient cytotoxicity against tumor cells without causing life-threatening cytokine release syndrome (CRS) or graft-versus-host disease (GvHD). When compared to chimeric antigen receptor (CAR) technology, Antibody-Cell Conjugation (ACC) technology has been developed to provide an efficient platform to arm immune cells with cancer-targeting antibodies to recognize and attack cancer cells. Recently, we established an endogenous CD16-expressing oNK cell line (oNK) with a favorabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 52 publications
(63 reference statements)
0
5
0
1
Order By: Relevance
“…此外,与NK细胞膜蛋白的氨基酸残基共价结合,也成为利用膜蛋白实现工程化修饰的一种策略。与上述非共价作用力比较,利用NK细胞膜蛋白的氨基酸残基反应形成稳定共价键,进行细胞表面修饰,提高了修饰的强度,使之具有更好的稳定性。然而,膜蛋白往往具备重要的生物功能,对其进行不可逆的共价改造有可能对细胞造成损害。因此,在偶联时要注意偶联的密度和空间位阻,以保障NK细胞正常的生物功能。NK细胞膜蛋白上有许多游离硫醇基团,可以采用马来酰亚胺-硫醇偶联的方法,实现药物释放与细胞杀伤的时空一致性。例如,利用胶束包载阿霉素,胶束的亲水端带有马来酰亚胺基团,与NK细胞表面巯基反应,构造了增强型NK细胞,当NK细胞与肿瘤细胞形成免疫突触释放酸性颗粒时,构成胶束的酸响应嵌段共聚物迅速质子化,胶束随即解离,释放化疗药物,协同杀伤靶细胞 [ 15 ] 。利用马来酰亚胺基团功能化的脂质体包载紫杉醇以实现对CAR-NK细胞的稳定偶联,该修饰在不影响NK细胞功能的情况下,同样实现了化疗药物向肿瘤部位的定向递送,协同增强了体内抗肿瘤疗效 [ 16 ] 。利用NK细胞膜蛋白的巯基还可以便捷地实现抗体-细胞偶联,如将市售乳腺癌药物曲妥珠单抗与NK细胞偶联可以实现对HER2阳性癌细胞的靶向杀伤 [ 17 ] 。…”
Section: Nk细胞表面修饰策略unclassified
“…此外,与NK细胞膜蛋白的氨基酸残基共价结合,也成为利用膜蛋白实现工程化修饰的一种策略。与上述非共价作用力比较,利用NK细胞膜蛋白的氨基酸残基反应形成稳定共价键,进行细胞表面修饰,提高了修饰的强度,使之具有更好的稳定性。然而,膜蛋白往往具备重要的生物功能,对其进行不可逆的共价改造有可能对细胞造成损害。因此,在偶联时要注意偶联的密度和空间位阻,以保障NK细胞正常的生物功能。NK细胞膜蛋白上有许多游离硫醇基团,可以采用马来酰亚胺-硫醇偶联的方法,实现药物释放与细胞杀伤的时空一致性。例如,利用胶束包载阿霉素,胶束的亲水端带有马来酰亚胺基团,与NK细胞表面巯基反应,构造了增强型NK细胞,当NK细胞与肿瘤细胞形成免疫突触释放酸性颗粒时,构成胶束的酸响应嵌段共聚物迅速质子化,胶束随即解离,释放化疗药物,协同杀伤靶细胞 [ 15 ] 。利用马来酰亚胺基团功能化的脂质体包载紫杉醇以实现对CAR-NK细胞的稳定偶联,该修饰在不影响NK细胞功能的情况下,同样实现了化疗药物向肿瘤部位的定向递送,协同增强了体内抗肿瘤疗效 [ 16 ] 。利用NK细胞膜蛋白的巯基还可以便捷地实现抗体-细胞偶联,如将市售乳腺癌药物曲妥珠单抗与NK细胞偶联可以实现对HER2阳性癌细胞的靶向杀伤 [ 17 ] 。…”
Section: Nk细胞表面修饰策略unclassified
“…Indeed, it has been recently shown that an adapted subpopulation of NK-92 expressing functional endogenous CD16 and further modified with the conjugation with Trastuzumab, an anti-human epidermal growth factor receptor 2 (HER-2) antibody, displayed enhanced cytotoxicity against HER-2-positive targets in vivo and in vitro. The absence of cell manipulation with viral vector or transposon systems, possibly mediating viral insertion mutation and imprecise chromosomal insertion, respectively, could represent an advantage with respect to other engineered products [ 145 , 146 ].…”
Section: Adoptive Transfer Of Nk Cellsmentioning
confidence: 99%
“…[ 16 ] Li and coworkers utilized a similar strategy to trastuzumab to oNK cell line. [ 17 ] Wei and coworkers designed a chimeric antibody‐nucleic acid T‐cell engager system with sophisticated programmable DNA nanoassemblies to bridge cancer cells and T cells. [ 18 ] Wu and coworkers used a fucosyltransferase to transfer a GDP‐modified IgG antibody to the glycocalyx on the surfaces of live cells.…”
Section: Introductionmentioning
confidence: 99%